1999
DOI: 10.1007/pl00006776
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate-Accumulating and Denitrifying Bacteria Isolated from Anaerobic-Anoxic and Anaerobic-Aerobic Sequencing Batch Reactors

Abstract: In this study, phosphate-accumulating bacteria achieved complete phosphate removal in two different systems: an anaerobic-anoxic sequencing batch reactor and an anaerobic-aerobic sequencing batch reactor. This result shows that phosphate-accumulating bacteria in the A2 SBR can use nitrate as terminal electron acceptor instead of oxygen. Phosphate-accumulating bacteria accumulated phosphate with a rates between 30 and 70 mg P/L/h in the A/O SBR and between 15 and 32 mg P/L/h in the A2 SBR. Twenty denitrifying i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 32 publications
(47 reference statements)
2
29
0
1
Order By: Relevance
“…Bacteria of the genus Bacillus have the activity for accumulating phosphorus in the form of polyphosphates (Merzouki et al 1999), and this phosphorus is then released during intracellular respiration (Couillard and Zhu 1993). In the study reported on in this paper, however, the variations in total and phosphate phosphorus concentrations were attributable not only to the activity of the microorganisms but also to the hydrolysis and reprecipitation of suspended solids.…”
Section: Phosphorus Removalmentioning
confidence: 66%
“…Bacteria of the genus Bacillus have the activity for accumulating phosphorus in the form of polyphosphates (Merzouki et al 1999), and this phosphorus is then released during intracellular respiration (Couillard and Zhu 1993). In the study reported on in this paper, however, the variations in total and phosphate phosphorus concentrations were attributable not only to the activity of the microorganisms but also to the hydrolysis and reprecipitation of suspended solids.…”
Section: Phosphorus Removalmentioning
confidence: 66%
“…Hascoet and Florentz (10), however, reported on a simultaneous uptake and release of phosphorus under anoxic conditions in the presence of an external carbon source, while van Niel et al (27) showed that, in the presence of nitrate, phosphorus release and acetate uptake by activated sludge organisms were severely inhibited. The studies described above, as well as most other studies on denitrification and phosphate removal in wastewater treatment plants (12,21), are based on the assumption that denitrifying PAOs with the physiological characteristics summarized in Table 1 are the only PAOs present in these environments. The present study demonstrates also that heterotrophic denitrifiers like P. denitrificans exhibit the ability to synthesize polyphosphate.…”
mentioning
confidence: 99%
“…These are denitrifying bacteria that under anaerobic conditions use nitrate as final acceptor electrons and have been found on SBR reactors converting all NO -3 in the medium to N 2 (Merzouki et al, 1999). Three others had similarity with uncultured bacterium clones isolated from the swine sludge.…”
Section: Resultsmentioning
confidence: 99%